(untitled) (Journal of Media studies, 2021)
Purpose of the research: One of the main purposes of the NewYork Convention was to serve international trade and commerce and to facilitatethe enforcement of an arbitral award in one of the Contracting States in otherStates. However, Article V (2) (b) allows a judge not to enforce a decision if itsexecution would be contrary to public policy. This article examines theexperience of resolving such cases in the United States, which is one of the mostimportant jurisdictions in international commerce. The purpose of this article isto consider how the concept of public policy is defined by the federal courts ofthe United States and applied in the context of the recognition and enforcementof arbitral awards. It first provides a brief analysis of the role of internationalarbitration in the US legal system, followed by a broad analysis of Americancase law. Methodology: formal logic, axiological methods, comparative legalmethod. Research findings: American courts are following an established liberal federal policy that favors the enforcement of foreign arbitral awards. Publicpolicy is interpreted in a very narrow manner.